Fabrication and characterization of continuous silver nanofiber/polyvinylpyrrolidone (AgNF/PVP) core–shell nanofibers using the coaxial electrospinning process. Issue 59 (6th June 2016) - Gebeyehu, Molla Bahiru; Chang, Yu-Hao; Abay, Angaw Kelemework; Chang, Shao-Yen; Lee, Jiunn-Yih; Wu, Chang-Mou; Chiang, Tai-Chin; Murakami, Ri-Ichi
Abstract : Core–shell silver nanofiber/polyvinylpyrrolidone (AgNF/PVP) nanofibers have been successfully fabricated via an efficient coaxial-spinneret electrospinning method with a vertical configuration using PVP and AgNO3 as precursor solutions. Abstract : In the present study, continuous and uniform core–shell silver nanofiber/poly(vinyl) pyrrolidone (AgNF/PVP) nanofibers have been successfully fabricated via an efficient coaxial-spinneret electrospinning method with a vertical configuration using PVP and AgNO3 as precursor solutions. PVP polymer was primarily used as a guide and provided an appropriate viscoelastic property by surrounding the AgNO3 (core) solution to fabricate aligned AgNF/PVP core–shell nanofibers. A series of AgNO3 concentrations were prepared by fixing the concentration of PVP as the shell fluid. The AgNO3 concentration had a significant influence on the formation of the continuous and uniform AgNF/PVP core–shell nanofiber structure and applied voltage had an effect on the formation of the compound stable Taylor cone. The (AgNF/PVP) core–shell nanofibers were formed via the stretching of the co-electrospinning jet and the reduction temperature for an appropriate time induced the silver nanofiber to be well aligned along the axis of the PVP-template electrospun fiber. The structure and properties of the thus obtained core–shell nanofibers were investigated thoroughly through optical microscopy (OM), transmission electron microscopy (TEM), focused ion beam (FIB), X-ray diffraction (XRD) and selected area electron diffraction (SAED). Energy dispersive spectroscopy (EDS) and X-ray photoelectron spectroscopy (XPS) were also employed to analyze the elemental composition of the core–shell nanofiber surface. On the other hand, UV-vis spectrophotometry was used to test the reduction of silver ions into metal silver. Moreover, electrical measurements were performed on the (AgNF/PVP) core–shell nanofibers, which indicated that the core–shell nanofibers became insulating due to the embedded highly conductive silver nanofibers by insulating the PVP shell. Therefore, coaxial electrospinning is a convenient and cost effective process for the fabrication of continuous and uniform (metal/polymer) core–shell nanostructure fibers.